Pillar data‐acquisition strategies for cryo‐electron tomography of beam‐sensitive biological samples - Parkhurst, JM; Varslot, T; Dumoux, M; Siebert, CA; Darrow, M; Basham, M; Kirkland, A; Grange, M; Evans, G; Naismith, JH (International Union of Crystallography, 2024)
For cryo‐electron tomography (cryo‐ET) of beam‐sensitive biological specimens, a planar sample geometry is typically used. As the sample is tilted, the effective thickness of the sample along the direction of the electron beam increases and the signal‐to‐noise ratio concomitantly decreases, limiting the transfer of information at high tilt angles. In addition, the tilt range where data can be collected is limited by a combination of various sample‐environment constraints, including the limited space in the objective lens pole piece and the possible use of fixed conductive braids to cool the specimen. Consequently, most tilt series are limited to a maximum of ±70°, leading to the presence of a missing wedge in Fourier space. The acquisition of cryo‐ET data without a missing wedge, for example using a cylindrical sample geometry, is hence attractive for volumetric analysis of low‐symmetry structures such as organelles or vesicles, lysis events, pore formation or filaments for which the missing information cannot be compensated by averaging techniques. Irrespective of the geometry, electron‐beam damage to the specimen is an issue and the first images acquired will transfer more high‐resolution information than those acquired last. There is also an inherent trade‐off between higher sampling in Fourier space and avoiding beam damage to the sample. Finally, the necessity of using a sufficient electron fluence to align the tilt images means that this fluence needs to be fractionated across a small number of images; therefore, the order of data acquisition is also a factor to consider. Here, an n‐helix tilt scheme is described and simulated which uses overlapping and interleaved tilt series to maximize the use of a pillar geometry, allowing the entire pillar volume to be reconstructed as a single unit. Three related tilt schemes are also evaluated that extend the continuous and classic dose‐symmetric tilt schemes for cryo‐ET to pillar samples to enable the collection of isotropic information across all spatial frequencies. A fourfold dose‐symmetric scheme is proposed which provides a practical compromise between uniform information transfer and complexity of data acquisition.